Reliability, Validity and Turkish Adaptation of Self-Directed Learning Scale (SDLS) - Zeynep İşıl Demircioğlu; Burak Öge; Emine Ezgi Fuçular; Tuğçe Çevik; Merve Denizci Nazlıgül; Erol Özçelik (International Journal of Assessment Tools in Education)
Self-Directed Learning Scale (SDLS) developed by Lounsbury, Levy, Park, Gibson, and Smith (2009) was used for determining individuals’ self-directed learning. The purpose of this study was to translatethe SDLSinto Turkish and to investigate its reliability and validity with a sample of272 university students. The SDLS, the Modified Schutte Emotional Intelligence Scale(MSEIS), Self-Directed Learning Inventory (SDLI), and the Causal UncertaintyScale (CUS) for determining convergent validity was applied to theparticipants. Factor analyses results verified the uni-dimensionality of the scale.The test–retest correlation of SDLS was 0.82, whereas Cronbach alpha coefficient of thescale was founded as 0.85 in the reliability analyses. Correlation coefficientsrepresenting for convergent validities varied from -0.30 to 0.72 (p < .01) and criterion validity ofthe scale was determined as 0.236 when cumulative GPA was used as criterionin the assessment of concurrent validity. The findings suggest that the Turkishadaptation of SDLS is a valid and reliable tool to measure self-directedlearning in Turkish samples.